Myocardial dysfunction and abnormalities in intracellular calcium handling in obese rats - Lima-Leopoldo, Ana Paula; Leopoldo, André S. [UNESP]; Sugizaki, Mário M.; Bruno, Alessandro [UNESP]; Nascimento, André F. [UNESP]; Luvizotto, Renata A.M. [UNESP]; Junior, Silvio A. Oliveira; Castardeli, Edson; Padovani, Carlos R. [UNESP]; Cicogna, Antonio C. [UNESP] (FapUNIFESP (SciELO), 2011)
Background: Several mechanisms have been proposed to contribute to cardiac dysfunction in obesity models, such as alterations in calcium (Ca 2+) handling proteins and β-adrenergic receptors. Nevertheless, the role of these factors in the development of myocardial dysfunction induced by obesity is still not clear. Objective: The purpose of this study was to investigate whether obesity induced by hypercaloric diets results in cardiac dysfunction. Furthermore, it was evaluated whether this functional abnormality in obese rats is related to abnormal Ca 2+ handling and the β-adrenoceptor system. Methods: Male 30-day-old Wistar rats were fed with standard food (C) and a cycle of five hypercaloric diets (Ob) for 15 weeks. Obesity was defined as increases in body fat percentage in rats. Cardiac function was evaluated by isolated analysis of the left ventricle papillary muscle under basal conditions and after inotropic and lusitropic maneuvers. Results: Compared with the control group, the obese rats had increased body fat and glucose intolerance. The muscles of obese rats developed similar baseline data, but the myocardial responsiveness to post-rest contraction stimulus and increased extracellular Ca 2+ were compromised. There were no changes in cardiac function between groups after β-adrenergic stimulation. Conclusion: Obesity promotes cardiac dysfunction related to changes in intracellular Ca 2+ handling. This functional damage is probably caused by reduced cardiac sarcoplasmic reticulum Ca 2+ ATPase (SERCA2) activation via Ca 2+ calmodulin kinase.
Keywords: Adrenergic; Beta; Calcium elevation; Myocardial dysfunction; Obesity; Rats; Receptors